PEMERIKSAAN UJI KERUTAN KULIT TERSTIMULASI EUTECTIC MIXTURE OF LOCAL ANAESTHETIC (EMLA) PADA POPULASI NORMAL - Arthur Hendrik Philips Mawuntu; Yoce Kurniawan; Meilany Feronika Durry; Herlyani Khosama (NEURONA, 2019)
EUTECTIC MIXTURE OF LOCAL ANAESTHETIC (EMLA) STIMULATED SKIN WRINKLING TEST IN NORMAL POPULATIONABSTRACTIntroduction: Peripheral neuropathy (PN) could reduce life quality among the affected individuals, while early detection is difficult, apparently healthy individuals could also be affected by this disorder. Stimulated skin wrinkling by eutectic mixture of local anaesthetic test (SSW-EMLA) and brief peripheral neuropathy screening (BPNS) are simple non- invasive examination to detect PN.Aims: To find out the percentage of asymptomatic neuropathy in the normal population using BPNS and SSW-EMLA.Methods: A cross-sectional study on a population that is considered as normal who come to R.D. Kandou Hospital Manado consecutively between October 2015 and September 2016. The normal population was based on modified healthy subject criteria by Lauria et al in a study about skin neural fiber morphometry. Brief peripheral neuropathy screening and SSW-EMLA were performed in all subjects. The Chi-square or Fisher exact test were used to assess between-group differences. P-value of 0.05 was considered statistically significance.Results: We enrolled 99 subjects, most of them were male (61.1%) and the median age was 31 years old. Asymptomatic neuropathy was found in 25.2% of the subjects. The highest neuropathy to non-neuropathy ratio was found in the >40 years old group (0,75). Stimulated skin wrinkling by eutectic mixture of local anaesthetic test could detect more cases compared to BPNS (24.2% vs 7.1%) and this finding was statistically significant.Discussion: The percentage of asymptomatic neuropathy in the normal population was 25.2% and mostly detected by SSW-EMLA compared to BPNS significantly.Keywords: Asymptomatic neuropathy, BPNS, normal population, SSW-EMLAABSTRAKPendahuluan: Neuropati perifer dapat menurunkan kualitas hidup penderitanya, namun deteksi dini masih sulit dilakukan, padahal orang-orang yang terlihat sehat juga dapat mengalaminya. Salah satu pemeriksaan non-invasif sederhana yang dapat dilakukan adalah stimulated skin wrinkling by eutectic mixture of local anaesthetic test (SSW-EMLA) selain skrining brief peripheral neuropathy screening (BPNS) yang biasa digunakan.Tujuan: Mengetahui persentase neuropati asimtomatik pada populasi normal menggunakan BPNS dan SSW- EMLA.Metode: Penelitian potong lintang terhadap populasi yang dianggap normal yang berobat di Instalasi Rawat Jalan RSUP Prof. Dr. R.D. Kandou secara konsekutif antara bulan Oktober 2015 sampai September 2016. Kriteria populasi normal berdasarkan modifikasi dari kriteria subjek sehat yang dibuat oleh Lauria dkk dalam penelitian tentang morfometri serabut saraf dermal kulit manusia. Subjek dilakukan pemeriksaan BPNS dan SSW-EMLA, lalu dinilai perbedaan antar kelompok dengan uji Chi-square atau Fisher’s exact. Nilai p=0,05 dijadikan batas kemaknaan statistik.Hasil: Terdapat 99 subjek yang sebagian besar adalah laki-laki (61,1%) dan median usia adalah 31 tahun. Neuropati asimtomatik ditemukan pada 25,2% subjek. Rasio mengalami dan tidak mengalami neuropati tertinggi ditemukan pada kelompok usia >40 tahun (0,75). Uji SSW-EMLA mampu mendeteksi lebih banyak kasus dibanding BPNS (24,2% vs7,1%) secara bermakna.Diskusi: Didapatkan 25,2% subjek neuropati asimtomatik pada populasi normal yang dominan ditemukan dengan uji SSW-EMLA dibandingkan BPNS secara bermakna.Kata kunci: BPNS, neuropati asimtomatik, populasi normal, SSW-EMLA